Susan Benson : art, design and craft on stage - Flood, Patricia (Firefly Books, 2019)
"A compelling and lavishly illustrated exploration of the work of one of Canada's most outstanding Theatrical Designers, this book is a detailed look at Susan Benson's illustrious career and approach to design for the stage. It includes 'behind the scenes' commentary, production photos and designs from many of her most significant productions over five decades in both Canada and the United States. These include: A Midsummer Night's Dream with Jessica Tandy and Maggie Smith, The Woman with Martha Henry, the National Ballet's Romeo and Juliet, Madam Butterfly and The Golden Ass for the Canadian Opera Company as well as the Stratford Festival's legendary productions of The Mikado, The Gondoliers, Iolanthe and many more."--$cProvided by publisher.